Perturbações cosmológicas num universo em aceleração transitória. - Vargas, Cristofher Zuñiga (2012)
Certain observational dates seem to indicate that the accelerated expansion of the Universe has already peaked and is now slowing down again. This could imply, that the accelerated expansion is a transient phenomenon and that there is a transition back to decelerated expansion. For a homogeneous and isotropic background, there exists a model that describes a transition from decelerated to accelerated expansion in the past (now well established according to the prevailing view) and an inverse transition from accelerated to decelerated expansion in the future. The present thesis also investigates the dynamics of the matter perturbations both on the Newtonian and GR levels and quanti es the potential relevance of perturbations of the dark-energy component. In the background, the model is tested against the Supernova type Ia (SNIa) data of the Constitution set and on the perturbative level against growth rate data and the data of the 2dFGRS project. Our results indicate, that a transient phase of accelerated expansion is not excluded by current observations.